Analisis penerapan nilai sosial dalam pembelajaran IPS siswa kelas V - Anisah Rofiatun; Jenny Indrastoeti Siti Poerwanti; Siti Istiyati (Didaktika Dwija Indria, 2025)
Abstract. This study explores the implementation of social values in the context of Social Studies (IPS) learning in an elementary school setting. Conducted at SDN Karangasem IV, this research adopts a qualitative descriptive approach through observation, interviews, and questionnaires. The findings reveal that teachers integrated social values such as honesty, tolerance, responsibility, politeness, discipline, and mutual assistance into their instructional strategies. These strategies include cooperative learning, individual assignments, face to face instruction, teacher modeling, and value based sanctions. The integration of these approaches has led to an observable improvement in students character development, as evidenced by their behavior both inside and outside the classroom. This study suggests that IPS learning can serve as an effective medium for character education when teachers consistently apply values in contextual and pedagogically sound ways.